Thermolysis of brown coal from the Baganursky deposit (Mongolia) - Kopylov, N.I. (KSU Publ., 2017)
The process of thermolysis of brown coal from the Baganursky deposit of Mongolia has been studied. These coals are characterized by high content of gas component (up to 40 %) and low content of liquid fraction. The decomposition begins at ~200 ºC. At temperatures up to ~700 ºC there is no sintering. In the solid residue, only relicts of the individual hydrocarbon constituents of the original coal are retained. The liquid condensate of sublimates (up to 19 % by weight of the initial) contains 0.78 % of the organic extract (96–98 % of the phenolic mass with a maximum boiling point of 360 °C) and 92.2 % of the aqueous solution (with a boiling range of 115–130 ºC). The initial aggregate state (the particle size of the material, the effect on it of the external medium) not only affects the yield of the gas constituent of coal during thermolysis, but also determines the impurity composition of the organic extract of the condensate liquid sublimates.
Баганур кен орнының (Монғолия) қоңыр көмірінің термолизі
Термолиз бурого угля Баганурского месторождения (Монголия)
Keywords: thermolysis; brown coals; solid residue; sublimates; condensate; hydrocarbons; phenols; thermal analysis